Decision-Making and Holistic Public Defense Post-Montgomery v. Louisiana. (July 2020) - Hussemann, Jeanette; Siegel, Jonah
In 2012, the U.S. Supreme Court ruled in Miller v. Alabama that mandatory sentences of life without the possibility of parole (LWOP) for youth are unconstitutional. In 2016, the Court held in Montgomery v. Louisiana that the ruling in Miller should be applied retroactively. Drawing from qualitative interviews with justice actors, and individuals who were sentenced to LWOP as juveniles and paroled, this article examines the implementation of Miller-Montgomery in Michigan, the factors that influence decisions to release juvenile lifers, and their reentry process. In doing so, we focus specific attention to the role of publicly appointed defense attorneys and the application of holistic defense practices to support Montgomery case mitigation and juvenile lifer reentry. Findings indicate that institutional disciplinary and programming records, emotional wellness, statements by victims' family members, political considerations, and reentry plans are key considerations when deciding whether a juvenile lifer should be eligible for parole.